STUDI KARAKTERISASI DAN KORELASI HIDROKARBON TERHADAP BATU LEMPUNG EOSEN-OLIGOSEN DI CEKUNGAN SUMATERA UTARA: POTENSI FORMASI PARAPAT SEBAGAI BATUAN INDUK - Budiman Ustiawan, Arief
Oil production in Indonesia has started since 1885 when the first oil well in Indonesia succeeded in production. The low recovery factor means that oil production in Indonesia has declined since 1995 due to a lack of exploration and investment in the petroleum sector. The oil production targets set by the government at the beginning of each year always fails to be achieved because most of the oil production in Indonesia comes from oil fields which are already included in the old field category. An integrated exploration effort is needed between geological, geophysical and hydrocarbon geochemical aspects to discover possible new hydrocarbon reserves in Indonesia. The high level of demand compared to the level of oil and gas production can cause an energy crisis. The North Sumatera Basin is one of the productive oil fields in Indonesia. The Baong and Bampo Formations with marine environments have been considered regional source rocks in the petroleum system in the North Sumatera Basin. However, several oil discoveries in the North Sumatera Basin tend to have lacustrine and fluvial environments based on hydrocarbon geochemical data. The formation that has a continental environment is the Parapat Formation. However, geochemical analysis has not been carried out in detail, especially on the Parapat Formation. Research was carried out on the Bampo and Parapat Formations in the North Sumatera Basin which are thought to have potential as source rocks. The data used is geochemical and geological data from 11 wells. The available geochemical data are Total Organic Carbon (TOC), Rock Eval Pyrolysis (REP), Vitrinite Reflectance (VR), Gas Chromatography (GC), and Gas Chromatography–Mass Spectrometry (GC-MS). The aim of this research is to determine the characteristics of the source rock, including quantity, quality, type and level of maturity and hydrocarbon character based on geochemical data in the Bampo and Parapat Formations.